Acute Exacerbation in Interstitial Lung Disease - Leuschner, Gabriela; Behr, Jürgen (Frontiers in Medicine, 2017)
Acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF) has been defined as an acute, clinically significant deterioration that develops within less than one month without obvious clinical cause like fluid overload, left heart failure or pulmonary embolism. Pathophysiologically, damage of the alveoli is the predominant feature of AE-IPF which manifests histopathologically as diffuse alveolar damage and radiologically as diffuse, bilateral ground-glass opacification on high-resolution computed tomography. A growing body of literature now focuses on acute exacerbations of interstitial lung disease (AE-ILD) other than IPF. Based on a shared pathophysiology it is generally accepted that AE-ILD can affect all patients with interstitial lung disease (ILD) but apparently occurs more frequently in patients with an underlying usual interstitial pneumonia pattern. The aetiology of AE-ILD is not fully understood, but there are distinct risk factors and triggers like infection, mechanical stress and microaspiration. In general, AE-ILD has a poor prognosis and is associated with a high mortality within 6-12 months. Although there is a lack of evidence based data, in clinical practice AE-ILD is often treated with a high dose corticosteroid therapy and antibiotics. This article aims to provide a summary of the clinical features, diagnosis, management and prognosis of AE-ILD as well as an update on the current developments in the field.